Associations between underlying diseases with COVID-19 and its symptoms among adults: a cross-sectional study - Wang, Binghan; Yuan, Shuyan; Ruan, Shuke; Ning, Xiuyuan; Li, Hanrui; Liu, Yuanhao; Li, Xiuyang (Frontiers in Public Health, 2023)
Background: Specific underlying diseases were reported to be associated with severe COVID-19 outcomes, but little is known about their combined associations. The study was aimed to assess the relations of number of and specific underlying diseases to COVID-19, severe symptoms, loss of smell, and loss of taste. Methods: A total of 28,204 adult participants in the National Health Interview Survey 2021 were included. Underlying diseases (including cardiovascular diseases, cancer, endocrine diseases, respiratory diseases, neuropsychiatric diseases, liver and kidney diseases, Fatigue syndrome, and sensory impairments), the history of COVID-19, and its symptoms were self-reported by structured questionnaires. Multivariable logistic regression models were used to assess the combined relation of total number of underlying diseases to COVID-19 and its symptoms, while mutually adjusted logistic models were used to examine their independent associations. Results: Among the 28,204 participants (mean ± standard deviation: 48.2±18.5 years), each additional underlying disease was related to 33%, 20%, 37%, and 39% higher odds of COVID-19 (odds ratio [OR]: 1.33, 95% confidence interval [CI]: 1.29-1.37), severe symptoms (OR: 1.20, 95% CI: 1.12-1.29), loss of smell (OR: 1.37, 95% CI: 1.29-1.46), and loss of taste (OR: 1.39, 95% CI: 1.31-1.49). In addition, independent associations of sensory impairments with COVID-19 (OR: 3.73, 95% CI: 3.44-4.05), severe symptoms (OR: 1.37, 95% CI: 1.13-1.67), loss of smell (OR: 8.17, 95% CI: 6.86-9.76), and loss of taste (OR: 6.13, 95% CI: 5.19-7.25), cardiovascular diseases with COVID-19 (OR: 1.13, 95% CI: 1.03-1.24), neuropsychiatric diseases with severe symptoms (OR: 1.41, 95% CI: 1.15-1.74), and endocrine diseases with loss of taste (OR: 1.28, 95% CI: 1.05-1.56) were observed. Conclusion: A larger number of underlying diseases were related to higher odds of COVID-19, severe symptoms, loss of smell, and loss of taste in a dose-response manner. Specific underlying diseases might be individually associated with COVID-19 and its symptoms.